AN ANALYSIS ON FACTORS INFLUENCING STUDENTS’ SPEAKING PERFORMANCE OF THE SECOND SEMESTER STUDENTS OF ENGLISH EDUCATION DEPARTMENT UNIVERSITAS RIAU - Areta, Dyah Pratiwi; Purwanti, Indah; Syafrianti, Maria (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: This research investigated factors influencing students’ speaking performance and students’ speaking problems and also identified the reasons why those factors were considered to influence students’ speaking performance. This was a descriptive research that used both quantitative and qualitative approaches. Using cluster random sampling, this research took 28 students of English Education Department, Universitas Riau in the academic year 2019/2020 as the sample of the research. The data were collected through closed-ended questionnaires, open-ended questionnaires, and semi-structured interviews. Data from all sources were triangulated to validate the data. The result of closed-ended questionnaires showed the factors influencing students’ speaking performance from the most influencing factors to the least one, as followed: (1) time for preparation and topical knowledge, (2) listeners’ support, (3) self-confidence, (4) feedback during speaking activity, (5) listening ability, (6) anxiety, (7) motivation to speak, (8) time allowed to perform a speaking task, and (9) pressure to perform well. Moreover, vocabulary mastery and interaction with native speakers were found to be other factors that were mentioned by the students. Furthermore, the research also showed the position of the speaking problems ranging from the problems that the most students encountered to the least one, as followed: (1) students used Indonesian language in English class, (2) they were worried about making mistakes, (3) they spoke very little or not at all, (4) students were shy to speak English, (5) they were fearful of criticism or losing face, (6) they could not think of anything to say in class, the last (7) students had no motivation to express themselves. Moreover, pronunciation issues were found to be another problem that was mentioned by the students.Keywords: Factors, Speaking Performance, Speaking Problems.